Homeostasis and Genotypic Resultant for the Main Spike Characters of Two-rowed Barely - Abdulkhaleq, Dana Azad (Sulaimani Journal for Pure and Applied Sciences, 2016)
Five genotypes of two-rowed barley (Hordeum distichum L.) named MORA, ABN- B, Arabi Aswad, Clipper and Bohoth H1 with their twenty F 1 progeny were evaluated in Kurdistan Region-Iraq at three different locations, Erbil-Grdarasha, Garmian-Kalar and Sulaimani-Qilyasan during the winter season 2011-2012 using Randomized Completely Block Design (RCBD) with three replications in order to study the homeostasis and genotypic resultant growth and spike characters. The results revealed highly significant effects due to genotypes × locations in most of the studied characters with exception of flag leaf length, spike length, and grin weight / spike. Parent 1 was the best genotype which had the highest homeostasis values for five characters no. of grain / spike (0.936), flag leaf length (0.915), peduncle diameter (0.962), spike length (0.933) and no. of spiklets / spike (0.975), while the hybrid (1×2) had the highest homeostasis values for three characters flag leaf length (0.985), spike length (0.988), and no. of spiklets / spike (0.990). So the homeostasis of these genotypes needs to be better evaluated in a set of environments tested across different years. Very high genotypic resultant values were obtained for no. of grain / spike (1.135 by the hybrid 2×5), flag leaf length (1.074 by the hybrid 5×4), spike length and no. of spikelets / spike (1.061 and 1.059, respectively by the hybrid 2×5) indicating these genotypes having high performances at different environments and should be not ignored in future studies.
Keywords: Tworowed barley; Homeostasis and Genotypic Resultant Analysis; Main spike characters